Laboratory measurements of vortex-induced sediment pickup rates - Cheng, Nian-Sheng (2016)
In the present study, vortices were generated in open channel flow with a cross-flow cylinder installed horizontally near the bed. Sediment pickup rates were then measured over the channel bed downstream the cylinder using a sediment lift. The experimental data show that the pickup rate increases exponentially in the presence of vortices. Two different relationships can be clearly observed between the pickup rate and the maximum root-mean-square (rms) value of the streamwise velocity fluctuation, one for the cylinder-obstructed flow and the other for the unobstructed flow. The results imply that the vortex-induced sediment pickup cannot be explained based on the traditional boundary layer theory.